Cronaca del convegno - Congress Report - Pszczolińska, Marta (Ciceroniana On Line, 2020)
Organised by the Ośrodek Badań nad Tradycją Antyczną [OBTA, Centre for Classical Tradition Studies], the Collegium Artes Liberales, the Cluster: The Past for the Present at the Faculty of "Artes Liberales" of the University of Warsaw and the Société Internationale des Amis de Cicéron (SIAC, Paris), the international conference Cicero, Society, and the Idea of artes liberales was held in Warsaw, focusing mainly on Cicero's importance in the formation of civil society through the reception, over the centuries, of his political, historiographic and educational thought in the context of the formation of the artes liberales. A special panel was dedicated to the presentation of the most recent studies on the Aratea. The conference took place on the 30th anniversary of the VIIth Colloquium Tullianum "Cicero and the State" organized in Warsaw in 1989 by Professor Jerzy Axer and the Center for Ciceronian Studies.